Salmonella–Host Interactions – Modulation of the Host Innate Immune System - Hurley, Daniel; McCusker, Matthew P.; Fanning, Séamus; Martins, Marta (Frontiers in Immunology, 2014)
Salmonella enterica (S. enterica) are Gram-negative bacteria that can invade a broad range of hosts causing both acute and chronic infections. This phenotype is related to its ability to replicate and persist within non-phagocytic host epithelial cells as well as phagocytic dendritic cells and macrophages of the innate immune system. Infection with S. enterica manifests itself through a broad range of clinical symptoms and can result in asymptomatic carriage, gastroenteritis, systemic disease such as typhoid fever and in severe cases, death (Gunn et al. 2014). Exposure to S. enterica serovars Typhi and Paratyphi exhibits clinical symptoms including diarrhoea, fatigue, fever and temperature fluctuations. Other serovars such as the non-typhoidal Salmonella (NTS), of which there are over 2,500, are commonly contracted as, but not limited to, food-borne sources causing gastrointestinal symptoms, which include diarrhoea and vomiting. The availability of complete genome sequences for many S. enterica serovars has facilitated research into the genetic determinants of virulence for this pathogen. This work has led to the identification of important bacterial components, including flagella, type III secretion systems, lipopolysaccharides and Salmonella pathogenicity islands, all of which support the intracellular life cycle of S. enterica. Studies focusing on the host-pathogen interaction have provided insights into receptor activation of the innate immune system. Therefore, characterising the host-S. enterica interaction is critical to understand the pathogenicity of the bacteria in a clinically relevant context. This review outlines salmonellosis and the clinical manifestations between typhoidal and NTS infections as well as discussing the host immune response to infection and the models that are being used to elucidate the mechanisms involved on Salmonella pathogenicity.